Therapeutic hypothermia in mild neonatal encephalopathy: a national survey of practice in the UK - Oliveira, Vânia; Singhvi, Dev Prya; Montaldo, Paolo; Lally, Peter J; Mendoza, Josephine; Manerkar, Swati; Shankaran, Seetha; Thayyil, Sudhin (Archives of disease in childhood. Fetal and neonatal edition, 2018)
Although major cooling trials (and subsequent guidelines) excluded babies with mild encephalopathy, anecdotal evidence suggests that cooling is often offered to these infants. We report a national survey on current cooling practices for babies with mild encephalopathy in the UK. From 74 neonatal units contacted, 68 were cooling centres. We received 54 responses (79%) and included 48 (five excluded due to incomplete data and one found later not to offer cooling). Of these, 36 centres (75%) offered cooling to infants with mild encephalopathy. Although most of the participating units reported targeting 33–34°C core temperature, seven (19%) considered initiating cooling beyond 6 hours of age and 13 (36%) discontinued cooling prior to 72 hours. Babies were ventilated for cooling in two (6%) units and 13 (36%) sedated all cooled babies. Enteral feeding was withheld in 15 (42%) units and reduced below 25% of requirements in eight (22%) units. MRI and neurodevelopmental outcome evaluation were offered to all cooled babies in 29 (80%) and 27 (75%) units, respectively. Further research is necessary to ensure optimal neuroprotection in mild encephalopathy.